Fire strike [large type] - Maden, Mike; Cussler, Clive (Cussler, Clive. Oregon files adventures ;, 2023)
"When Cabrillo is hired to extract an undercover operative in Kenya, he finds himself on the trail of a deadly international plot. A Saudi Prince seeks to spark a new war in the Middle East, and ultimately destroy Israel. Cabrillo's crew of the Oregon have met their most fearsome adversaries yet: a force of bio-hacked soldiers endowed with extreme strength and stamina and an unquenchable appetite for violence. The Oregon team must journey from the Amazon rainforest to an abandoned monastery in Eritrea before a final showdown in the mountains of Yemen to disable a ship-killer missile before the Arabian Sea becomes a mass grave"--